Intrahepatic cholangiocarcinoma mimicking a liver abscess. Issue 12 (3rd August 2020) - Yacoub, Haythem; Hassine, Hajer; Boukriba, Seif; Haouet, Slim; Ayari, Asma; Kchir, Hela; Maamouri, Nadia
Abstract: Intrahepatic cholangiocarcinoma masquerading as liver abscess, and presenting with fever, is a very rare situation and should be considered in nonresolving liver abscess. Only few cases were reported in the literature. This entity is characterized by late diagnosis and poor prognosis. Abstract : Intrahepatic cholangiocarcinoma masquerading as liver abscess, and presenting with fever, is a very rare situation and should be considered in nonresolving liver abscess. Only few cases were reported in the literature. This entity is characterized by late diagnosis and poor prognosis.